The effect of vegetable biogenic additives on microbiological indicators of rye-wheat crispbreads dough - E. V. Belokurova; E. N. Mishina; T. V. Alexeeva (Новые технологии, 2019)
The article presents the results of the research of the possibility of using extracts of ginger root and calendula flowers in the production of crispbreads from a mixture of rye and wheat flour added to the dough, in order to reduce the process of dough process and to impart functional properties to finished products. The extracts have been obtained under optimal conditions, selected experimentally, from crushed raw ginger root or calendula flowers. The optimal parameters of the process of extraction of medicinal plants and indicators of microbiological safety of plant extracts have been determined. It has been established that these extracts can be recommended as mass consumption foods in order to give them antioxidant properties, increase storage capacity and expand the assortment in this segment.The effect of these plant extracts on the viability of yeast colonies during the fermentation of dough for rye-wheat crispbreads has been established. The fermentation process and accumulation of yeast mass intensify when the extracts are added to the dough. It can be concluded that extracts of medicinal plants are an additional nutrient medium for yeast colonies due to the introduction of macro- and microelements with them.